Determinants Of Accrual Manipulation In Local Government Financial Reporting: Empirical Evidence From The Covid-19 Pandemic - Meisi Ikrima; Syukriy Abdullah (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study examines the determinants of accrual manipulation in local government financial reporting in Indonesia during 2020, a year marked by the COVID-19 pandemic, repeated budget revisions, and severe fiscal pressures. A quantitative approach was employed using secondary data from the audited Local Government Financial Statements issued by the Audit Board of Indonesia (BPK RI). The final sample consisted of 85 local governments after removing outliers to satisfy the normality test. The regression model is statistically significant (F = 3.731; p = 0.008) with R² of 0.157, indicating that four independent variables explain 15.7% of the variance in accrual manipulation. Partially, Government Size has a positive and significant effect (β = 0.057; p < 0.02), while Fiscal Capacity has a negative and significant effect (β = −0.070; p < 0.02). Fiscal Stress and Budget Surplus (SiLPA) each of them show positive and negative but insignificant effects. The findings reveal that larger local governments face higher bureaucratic complexity and political pressure, broadening discretionary room for accrual manipulation. Conversely, strong fiscal capacity reduces opportunistic reporting incentives. These results reinforce agency theory in the context of public finance and suggest implementing risk-based audits and strengthening local accounting capacity to enhance financial transparency and accountability.